2022
DOI: 10.3390/ma15124277
|View full text |Cite
|
Sign up to set email alerts
|

Research, Modelling and Prediction of the Influence of Technological Parameters on the Selected 3D Roughness Parameters, as Well as Temperature, Shape and Geometry of Chips in Milling AZ91D Alloy

Abstract: The main purpose of the study was to define the machining conditions that ensure the best quality of the machined surface, low chip temperature in the cutting zone and favourable geometric features of chips when using monolithic two-teeth cutters made of HSS Co steel by PRECITOOL. As the subject of the research, samples with a predetermined geometry, made of AZ91D alloy, were selected. The rough milling process was performed on a DMU 65 MonoBlock vertical milling centre. The machinability of AZ91D magnesium al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…A generalizable yet strong relationship cannot be observed for the Sku parameter based on the present experimental results. This result confirms the findings of [34].…”
Section: Discussion Of the Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…A generalizable yet strong relationship cannot be observed for the Sku parameter based on the present experimental results. This result confirms the findings of [34].…”
Section: Discussion Of the Resultssupporting
confidence: 92%
“…Peng et al compared additively manufactured parts, upon which heat treatment was and was not applied, and found that the Ssk and Sku parameters are suitable for the characterization of the surfaces [33]. According to Kulis et al, who analyzed milled surfaces, the peak height (Sp), Ssk, and Sku parameters provide no clear information on the effects of the cutting parameters [34]. Karmiris-Obratanski et al carried out an in-depth analysis of the Ssk connected to surfaces machined by electro-discharge machining and found that Ssk is not significantly influenced by the machining parameters [35].…”
Section: Introductionmentioning
confidence: 99%
“…In order to conduct a study on the innovative post-weld finishing effect in steel specimens produced using different welding methods and its impact on the key surface quality parameters, the 2D and 3D surface roughness measurements were performed [ 13 , 14 , 15 , 16 , 17 ]. The level of selected surface roughness parameters determined its functional properties: fatigue strength, wear and corrosion resistance, contact strength, tribological properties, adhesion, and others.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of variance (ANOVA) was performed to evaluate the arranged formula. Kulisz et al 18 measured machinability indices, for example, 3D roughness parameters, chip temperature, chip shape and geometry. Then analysed the machinability of AZ91D magnesium alloy.…”
Section: Introductionmentioning
confidence: 99%